ЩОДО ПІДСТАВ ВИЗНАННЯ ПРИЛЮДНИХ ТОРГІВ/АУКЦІОНУ З РЕАЛІЗАЦІЇ АРЕШТОВАНОГО МАЙНА НЕДІЙСНИМИ - Pavlyuchenko, Y.N. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The paper analyses scientific literature, current legislation, materials of judicial practice in order to specify the grounds for confession of public sales/auction on realization of arrested property to be invalid. Provisions of current legislation, which set the rules of organization and conduction of public sales/auction and which can be the grounds for confession them to be invalid, are investigated. The attention is paid to investigation of the problem concerning involvement of violations of the state performer into the list of such grounds. As a result, the list of grounds for confession of public sales/auction on realization of arrested property to be invalid has been specified; recommendations have been worked out to fix them in the legislation.